If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 3) = 17 Reorder the terms: 3(3 + 4x) = 17 (3 * 3 + 4x * 3) = 17 (9 + 12x) = 17 Solving 9 + 12x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 12x = 17 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = 17 + -9 12x = 17 + -9 Combine like terms: 17 + -9 = 8 12x = 8 Divide each side by '12'. x = 0.6666666667 Simplifying x = 0.6666666667
| 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 | | F(x)=x^3+2x^2+x+4 | | 2n-1=-10 | | 11=4(x-1)-x | | 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x | | 2+.142x=9 | | 3b-2=14 | | 2a-7=4(3a+1)-2 | | -6x-x+10=16-7x-5 | | 3x-5(x-5)=-7+4x-16 | | (-3)(-2)+(-2)(4)= | | 12+5x=-2x-11 | | 13=1-7x-5x | | X^2-15x-1000=0 | | (7y+x)=4 | | y=3x^3+27x^2 | | 8(x+4)=7(2x+3) | | 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w |